Skin-to-skin contact between mothers and full-term newborns after birth: a cross-sectional study - Rosely Sayuri Kuamoto; Mariana Bueno; Maria Luiza Gonzalez Riesco (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze skin-to-skin contact practice in full-term newborns after birth. Method: a cross-sectional study carried out in São Paulo-SP with 78 mother-child binomials. Data were obtained from medical records and by non-participant observation. Maternal, neonatal and care conditions, length of skin-to-skin contact and breastfeeding attachment were analyzed. Results: skin-to-skin contact was performed in 94.9% of births, with a mean length of 29 minutes. Births with intact perineum took longer, neonates with Apgar 10, without upper airway aspiration, assisted by a nurse-midwife and with neonatal assistance by a resident in pediatrics. The variables that favor breastfeeding attachment were perineal integrity, newborn with good vitality, without upper airway aspiration and who received professional assistance for breastfeeding attachment. Conclusion: skin-to-skin contact was performed in almost all births, but with less time than recommended as best practice.